MANAGEMENT OF SUSTAINABLE DEVELOPMENT AND ENVIRONMENTAL PROTECTION - Sanja Smolovic\'; Slaana Zivanovic\'; Nikola Abramovic\'; Miodrag Zivanovic\' (Agora International Journal of Economical Sciences (AIJES), 2023)
Unifying the concept of social, economic and ecological development, the new development paradigm was established under the name of sustainable development. Sustainable development should harmonize sensible consumption of natural resources with their protection and ensure a more equitable division of wealth and equal economic development at the global level. Within such a context, science and environmental education constitute the precondition for our joint future. As regards the contents, this paper provides a precise and comprehensive overview of theoretical features of environmental pollution and sustainable development, as well as the most important aspects of environmental and natural resource management. For effective control of environmental pollution to be possible, it is necessary to consider the ethical foundations of environmental economics in particular, and special attention is paid to in the paper. A significant part of this work is devoted to criticism of uncontrolled economic growth and the inefficiency of the state in controlling environmental pollution. Knowledge management for the purpose of sustainable development and development of international regulations on the environment are also included.
Keywords: 330